Dental Care in Piauí's Rural Area: Extension collaborating with academic experience (Research, Society and Development, 2020)
The National Oral Health Policy aims to increase access to dental care in socially vulnerable areas; however, structural, political, economic and environmental factors interfere with the dentist's full performance, intensifying social disparities. In the concept of preventive dentistry, health promotion provides the population with tools to improve quality of life, in addition to making the patient an active agent in this transformation. In this context, the academic experience outside the walls has the tool to bring students closer to the social realities that surround them, as it has an active methodology in health education that generates benefits for the community that will interact with the academic team, and for the future professional who will know reconcile theories and scientific techniques with different socio-environmental structures. Thus, the objective of this article is to report the academic experience of dentistry students who worked in rural Piauí as extension workers in the PERES project. The performance of the oral health team included prevention, promotion and health recovery, where students experienced challenges in the face of the community reality, such as high prevalence of caries in children, periodontal disease in adults and poorly adapted prostheses in the elderly. Thus, through contact with the community, social perceptions were formulated in dental care and the development of comprehensive and humanitarian health in the training of future dentists.